Architecture of Indonesias Checks and Balances - Chandranegara, Ibnu Sina (Constitutional Review, 2016)
Research on "checks and balances" in legal studies often raises high quality questions such as, is the checks and balances a doctrine, principle, or legal theory, or maybe precisely the formula of power in politics. History has been recorded that in any discussions regarding the formation of the constitutional separation, division and smelting power is something that is popular to be discussed before and even after becoming the constitution. Therefore, the casting of checks and balances into the constitution is an interesting study to determine the portion and posture. This study used using legal normative methodology. In addition, comparative studies on constitution was conducted using classic and modern constitutional law literature. Several approaches were used on this research such as, historical, political, economical approach on understanding the practice on checks and balance which stated in constitutions in some countries.